Public Service Innovation through Digital Governance: Analysis of Public Administration Transformation - Rahma Alhasni; Asna Aneta (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to analyze the implementation of digital-based public service innovations, map empirical findings, and identify research and theoretical gaps in the context of bureaucratic digitalization. This study focuses on public service innovations through digital governance as part of public administration transformation in Indonesia. The urgency of this study is to address the challenges of traditional bureaucracy, which is considered slow, non-transparent, and unresponsive to the needs of the community. Theoretically, this study is based on the New Public Management (NPM) and Digital Era Governance (DEG) frameworks, which emphasize efficiency, transparency, integration, and public participation. The method used is a Systematic Literature Review (SLR) with PRISMA guidelines, covering the stages of identification, selection, evaluation, and synthesis of literature. The research sources came from accredited national journal articles and relevant scientific proceedings published between 2020 and 2025, with a focus on the digital-based public service sector. The data was analyzed narratively and thematically to group findings based on phenomena, institutions, policies, service models, and the implications of bureaucratic transformation. The results of the study show that the digitization of public services increases effectiveness, transparency, and accessibility, as demonstrated by the SIANTON, JAKI, Siskeudes, and SPBE applications. However, there are still obstacles in the form of limited infrastructure, digital literacy, human resource readiness, and weak inter-agency integration. In conclusion, public service innovation through digital governance has a strategic role in accelerating public administration transformation. However, successful implementation requires institutional support, regulation, and community participation so that the digital bureaucracy can develop in an adaptive, inclusive, and sustainable manner.